Characterization and performance evaluation of electrodeposition synthesized cobalt-nickel layered double hydroxide and composites for high-efficiency hybrid capacitor applications - Manyala, Ncholu I. (University of Pretoria, 2022)
Thesis (PhD (Physics))--University of Pretoria, 2022.